Distribution state estimation incorporating load modelling - Karimi, M.; Mokhlis, Hazlie; Bakar, A.H.A.; Shahriari, A.; Kazeminejad, M. (Przeglad Elektrotechniczny, 2012)
An accurate system state monitoring is crucial for maintaining system security, reliability and quality of a power system network. The process for assessing the system state variables can be achieved by state estimation method. State estimation is an action of appraising an unknown system variables based on limited number of real-time measurements. In this paper, state estimation for a distribution network is developed and enhanced by incorporating composite load model. By incorporating this model, the calculated state variables of the network will be more accurate (to obtain the most practical value of the system state variables). The proposed state estimation results are compared with backwardforward sweep load flow technique to justify the system state variables.